2016
DOI: 10.3138/ptc.2014-66
|View full text |Cite
|
Sign up to set email alerts
|

Allocation of Rehabilitation Services for Older Adults in the Ontario Home Care System

Abstract: Background: Physiotherapy and occupational therapy services can play a critical role in maintaining or improving the physical functioning, quality of life, and overall independence of older home care clients. Despite their importance, however, there is limited understanding of the factors that influence how rehabilitation services are allocated to older home care clients. The aim of this pilot study was to develop a preliminary understanding of the factors that influence decisions to allocate rehabilitation th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
5
0
1
Order By: Relevance
“…This coincides with research findings that indicate that OT is primarily used for home assessment purposes in the Ontario Home Care System [48]. This finding also corresponds with a recent review of American home care services that found adaptation and environment as the most frequently referenced intervention [49].…”
Section: Discussionsupporting
confidence: 84%
“…This coincides with research findings that indicate that OT is primarily used for home assessment purposes in the Ontario Home Care System [48]. This finding also corresponds with a recent review of American home care services that found adaptation and environment as the most frequently referenced intervention [49].…”
Section: Discussionsupporting
confidence: 84%
“…Está demonstrado que, quanto mais as pessoas envelhecem, mais cuidados de saúde no domicílio vem associados às suas necessidades individuais de saúde uma prioridade fundamental (Hoeck, et al, 2011). Barbosa A sugestão que é feita no Canadá foca a optimização dos serviços de reabilitação, de forma a fazer chegar estes serviços aos idosos, e a promover que os mesmos sejam cada vez mais úteis para as pessoas e famílias que recorrem ao SAD (Armstrong, Sims-Gould, & Stolee, 2016).…”
Section: Discussionunclassified
“…Home rehabilitation services help aging adults improve or maintain their quality of life, physical function and independence; in doing so it extends their time in the community and away from hospitals [ 24 , 25 ]. Despite this evidence, many clients who could benefit from home rehabilitation services do not receive them [ 26 ] and virtual rehabilitation can play a key role in this solution. The advantages of virtual rehabilitation discussed here, including cost-effectiveness and provision of care to remote areas not accessible to standard care, can increase health care quality and availability for all and support healthy aging in place.…”
Section: The Debate: Will Virtual Rehabilitation Replace Clinicians?mentioning
confidence: 99%